Central Nervous System Inflammatory Aggregates in the Theiler's Virus Model of Progressive Multiple Sclerosis - DiSano, Krista D.; Royce, Darlene B.; Gilli, Francesca; Pachner, Andrew R. (Frontiers in Immunology, 2019)
Persistent central nervous system (CNS) inflammation, as seen in chronic infections or inflammatory demyelinating diseases such as Multiple Sclerosis (MS), results in the accumulation of various B cell subsets in the CNS, including naïve, activated, memory B cells (Bmem), and antibody secreting cells (ASC). However, factors driving heterogeneous B cell subset accumulation and antibody (Ab) production in the CNS compartment, including the contribution of ectopic lymphoid follicles (ELF), during chronic CNS inflammation remain unclear and is a major gap in our understanding of neuroinflammation. We sought to address this gap using the Theiler’s murine encephalomyelitis virus-induced demyelinating disease (TMEV-IDD) model of progressive MS. In this model, injection of the virus into susceptible mouse strains results in a persistent infection associated with demyelination and progressive disability. During chronic infection, the predominant B cell phenotypes accumulating in the CNS were isotype-switched B cells, including Bmem and ASC with naïve/early activated and transitional B cells present at low frequencies. B cell accumulation in the CNS during chronic TMEV-IDD coincided with intrathecal Ab synthesis in the cerebrospinal fluid (CSF). Mature and isotype-switched B cells pre¬dominately localized to the meninges and perivascular space, with IgG isotype-switched B cells frequently accumulating in the parenchymal space. Both mature and isotype-switched B cells and T cells occupied meningeal and perivascular spaces, with minimal evidence for spatial organization typical of ELF mimicking secondary lymphoid organs (SLO). Moreover, immunohistological analysis of immune cell aggregates revealed a lack of SLO-like ELF features, such as cell proliferation, cell death, and germinal center B cell markers. Nonetheless, flow cytometric assessment of B cells within the CNS showed enhanced expression of activation markers, including moderate upregulation of GL7 and expression of the costimulatory molecule CD80. B cell-related chemokines and trophic factors, including APRIL, BAFF, CXCL9, CXCL10, CCL19, and CXCL13, were elevated in the CNS. These results indicate that localization of heterogeneous B cell populations, including activated and isotype-switched B cell phenotypes, to the CNS and intrathecal Ab (ItAb) synthesis can occur independently of SLO-like follicles during chronic inflammatory demyelinating disease.